Patients From Distressed Communities Who Undergo Surgery for Hip Fragility Fractures Are Less Likely to Have Advanced Care Planning Documents in Their Electronic Medical Record. Issue 2 (16th February 2023) - Khan, Irfan A.; Magnuson, Justin A.; Ciesielka, Kerri-Anne; Levicoff, Eric A.; Cohen-Rosenblum, Anna; Krueger, Chad A.; Fillingham, Yale A.
Abstract: Background: Advanced care planning documents provide a patient's healthcare team and loved ones with guidance on patients' treatment preferences when they are unable to advocate for themselves. A substantial proportion of patients will die within a few months of experiencing a hip fracture, but despite the importance of such documents, patients undergoing surgery for hip fracture seldom have discussions documented in the medical records regarding end-of-life care during their surgical admission. To the best of our knowledge, the proportion of patients older than 65 years treated with surgery for hip fractures who have advanced care planning documents in their electronic medical record (EMR) has not been explored, neither has the association between socioeconomic status and the presence of those documents in the EMR. Determining this information can help to identify opportunities to promote advanced care planning. Questions/purposes: (1) What percentage of patients older than 65 years who undergo hip fracture surgery have completed advanced care planning documents uploaded in the EMR before or during their surgical hospitalization, or at any timepoint (before admission, during admission, and after admission)? (2) Are patients from distressed communities less likely to have advanced care planning documents in the EMR than patients from wealthier communities, after controlling for economic well-being as measured by the Distressed Communities Index? (3) What percentage of patients older than 65 years with hip fractures who died during their hospitalization for hip fracture surgery had advanced care planning documents uploaded in the EMR? Methods: This was a retrospective, comparative study conducted at two geographically distinct hospitals: one urban Level I trauma center and one suburban Level II trauma center. Between 2017 and 2021, these two centers treated 850 patients for hip fractures. Among those patients, we included patients older than 65 years who were treated with open reduction and internal fixation, intramedullary nailing, hemiarthroplasty, or THA for a fragility fracture of the proximal femur. Based on that, 83% (709 of 850) of patients were eligible; a further 6% (52 of 850) were excluded because they had codes other than ICD-9 820 or ICD-10 S72.0, and another 2% (17 of 850) had incomplete datasets, leaving 75% (640 of 850) for analysis here. Most patients with incomplete datasets were in the prosperous Distressed Communities Index category. Among patients included in this study, the average age was 82 years, 70% (448 of 640) were women, and regarding the Distressed Communities Index, 32% (203 of 640) were in the prosperous category, 25% (159 of 640) were in the comfortable category, 15% (99 of 640) were in the mid-tier category, 5% (31 of 640) were in the at-risk category, and 23% (145 of 640) were in the distressed category. The primary outcome included the presence of advanced care planning documents (advanced directives, healthcare power of attorney, or physician orders for life-sustaining treatment) in the EMR before surgery, during the surgical admission, or at any time. The Distressed Communities Index was used to indicate economic well-being, and patients were identified as being in one of five Distressed Communities Index categories (prosperous, comfortable, mid-tier, at-risk, and distressed) based on ZIP Code. An exploratory analysis was conducted to determine variables associated with the presence of advanced care planning documents in the EMR. A multivariate regression was then performed for patients who did or did not have advanced care planning documents in their medical record at any time. The results are presented as ORs with the associated 95% confidence interval (CI). Results: Nine percent (55 of 640) of patients had advanced care planning documents in the EMR preoperatively or during their surgical admission, and 22% (142 of 640) of patients had them in the EMR at any time. After controlling for potential confounding variables such as age, laterality (left or right hip), hospital type, and American Society of Anesthesiologists (ASA) classification, we found that patients in Distressed Communities Index categories other than prosperous had ORs lower than 0.7, with patients in the distressed category (OR 0.4 [95% CI 0.2 to 0.7]; p < 0.01) and comfortable category (OR 0.5 [95% CI 0.3 to 0.9]; p = 0.01) having a substantially lower odds of having advanced care planning documents in their EMR. Patients aged 86 to 95 years (OR 1.9 [95% CI 1.1 to 3.4]), those 96 years and older (OR 4.0 [95% CI 1.7 to 9.5]), and those with a higher ASA classification (OR 1.6 [95% CI 1.1 to 2.3]) had a higher odds of having advanced care planning documents in the EMR at any time. Among 14 patients who experienced in-hospital mortality, two had advanced care planning documents uploaded into their EMR, whereas 12 of 14 who died in the hospital did not have advanced care planning documents uploaded into their EMR. Conclusion: Orthopaedic surgeons should counsel patients regarding the risk for postoperative complications after fragility hip fracture surgery and engage in shared decision-making regarding advanced care planning documents with patients or, if the patients are unable, with their families. Additionally, implementing virtual education about advanced care planning documents and using easy-to-read forms may facilitate the completion of advanced care planning documents by patients older than 65 years, especially patients with low economic well-being. Limitations of this study include having a restricted number of patients in the at-risk and mid-tier Distressed Communities Index categories and a restricted number of patients identifying as non-White races/ethnicities. Future research should evaluate the effect of advanced care document presence in the EMR on end-of-life care intensity in patients treated for fragility hip fractures. Level of Evidence: Level III, therapeutic study.